The Effect of Gaze Stability Exercise Intervention on Increasing Dynamic Balance in the Elderly - Lina, Ratu Karel; Ningrum, Olivia Filziah; Sariana, Erna; Manurung, Santa; ., Wartonah (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Physiological changes from decreased muscle strength, posture change, somatosensory system (visual, vestibular, proprioception) causes balance disorders in elderly. Gaze stability exercise is a proper exercise since it is based on pathophysiology of elderly imbalance caused by aging of sensory system and skeletal muscle. Objective: to find out the effect of Gaze Stability Exercise Intervention on increasing dynamic balance in elderly. Method: a pre-experimental with one group pre-posttest design. There were 11 elderly as samples selected with purposive sampling technique. Intervention was done twice a week for four weeks with duration of 60 minutes. Dynamic balance measurement used Time Up and Go Test (TUGT). Data analysis used was paired- t test. Result: The average time up and go test before intervention was 17.82 and after invention was 13.82.the result of before and after statistical test showed p value of 0.000 (p<0.05). Conclusion: There is an effect of Gaze Stability Exercise Intervention on increasing dynamic balance in elderly